2010
DOI: 10.1099/mic.0.040139-0
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus rhamnosus GG attenuates interferon-γ and tumour necrosis factor-α-induced barrier dysfunction and pro-inflammatory signalling

Abstract: The intestinal epithelium forms a protective barrier against luminal contents and the external environment, mediated via intercellular tight junctions (TJs). The TJ can be disrupted via cell signalling induced by either enteric pathogens or pro-inflammatory cytokines, thereby contributing to various intestinal disorders ranging from acute infectious diarrhoea to chronic inflammatory bowel diseases. Probiotics, such as Lactobacillus rhamnosus GG (LGG), are reported to confer beneficial effects on epithelial cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
129
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(141 citation statements)
references
References 44 publications
8
129
1
1
Order By: Relevance
“…Additionally, L. rhamnosus GG has been demonstrated to inhibit NF-B signaling, which led to enhanced barrier integrity in a model of cytokine-induced barrier dysfunction (5). The soluble factor p40, derived from L. rh-amnosus GG, has also been implicated in protection of the gut epithelial barrier from peroxide-induced damage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, L. rhamnosus GG has been demonstrated to inhibit NF-B signaling, which led to enhanced barrier integrity in a model of cytokine-induced barrier dysfunction (5). The soluble factor p40, derived from L. rh-amnosus GG, has also been implicated in protection of the gut epithelial barrier from peroxide-induced damage.…”
Section: Discussionmentioning
confidence: 99%
“…Ingestion of probiotic bacteria has been claimed to prevent or treat a variety of disorders of the gut, ranging from travelers' diarrhea to the chronic relapsing inflammatory condition Crohn's disease (1, 2) through mechanisms that are incompletely understood. However, evidence suggests that one mechanism may be via protection or augmentation of gut epithelial barrier function (3,4,5). This is provided for in the most part by tight junctions (TJs), which are multiprotein complexes sealing the paracellular space between adjacent epithelial cells and limiting transport through this pathway to small, hydrophilic molecules and ions (reviewed in reference 6).…”
mentioning
confidence: 99%
“…Tight junctions are the major determinants of paracellular permeability. Although changes in epithelial tight junction protein expression have been studied extensively in monolayers stimulated by cytokines, challenged by bacteria, or exposed to aspirin (16)(17)(18)(19)(20)(21)(22), much remains to be understood about barrier disruptive changes under inflammatory conditions in vivo. Our results have indicated that the probiotic mixture VSL#3 protects colonic epithelial barrier function in acute DSS colitis, as demonstrated by effective prevention of increased Evans blue dye uptake.…”
Section: Discussionmentioning
confidence: 99%
“…A number of health benefits have been claimed for Lact. rhamnosus, such as alleviation of inflammation or pathogen-induced barrier dysfunction (Lebeer et al 2010, Donato et al 2010, prevention of intestinal injuries induced by rotavirus diarrhea (Liu et al 2013a), a decrease in the symptoms of atopic dermatitis in children aged 4-48 months (Wu et al 2015) and prevention of gastrointestinal infectious (Hojsak et al 2010).…”
mentioning
confidence: 99%